The European Union’s axiological credo and morality policy tensions - Gierycz, Michał (Studia Philosophiae Christianae, 2017)
Since the beginning of 21st century we have witnessed growing discussion on fundamental values (life, marriage, sexual education, freedom of conscience) within the European Union (the EU). The aim of this paper is to discuss the interconnection between those morality policy challenges and the EU’s axiology. As the EU’s value credo was formulated when moral struggles in European countries were already very intensive, the paper analyses if and how European cultural tensions are reflected in the primary law of the EU, as well as how the solutions adopted in the Treaty on the EU work in the political practice. To reveal the context and peculiarity of the solutions adopted within the EU, paper starts with some remarks on the approach to values typical of the constitutional traditions of the European states and shortly presents their reaction to moral challenges of late modernity. The main theoretical thesis presented here is that the current way of axiological thinking presented in the EU does no longer follow the natural law approach but tries to find its own peculiar axiological way by staying open to a different, not rarely opposite, understanding of fundamental moral values. Its peculiarity is to be observed at two levels: the level of axiology (what values are at stake?), as well as at the level of metaaxiology (what is the source of those values?). Analyses of EU policy reveal practical outcomes of such a “relativistic shift” for interpretation of values and morality policy of the EU.